2013
DOI: 10.13157/arla.60.1.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use of Food Resources Between the Kelp GullLarus dominicanusand the Threatened Olrog's GullL. atlanticus

Abstract: We assessed the potential overlap in diet composition of the kelp gull Larus dominicanus and the threatened Olrog's gull L. atlanticus breeding syntopically at Bahía San Blas, Argentina, during two breeding seasons (2006 and 2007). Diet was studied using regurgitated pellets (180 per species and year) and chick stomach samples obtained through the water offloading technique (60 per species only in 2007). Kelp gulls fed on at least 18 prey types. Fish was the most important diet component (73.3-85%, depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
1
14
0
6
Order By: Relevance
“…Both parasite species analysed co-occurred in the kelp gull L. dominicanus , albeit in different individuals. This result can be a consequence of the generalist foraging behaviour of kelp gulls, which take advantage of the multiple trophic resources available along the coast from both marine and estuarine habitats (Bahamondes & Castilla, 1986; Yorio et al ., 2013). Accordingly, kelp gulls present a high diversity of endoparasites, including cestodes, nematodes, trematodes and acanthocephalans (Torres et al ., 1991; Riquelme et al ., 2006; González-Acuña et al ., 2009; Diaz et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both parasite species analysed co-occurred in the kelp gull L. dominicanus , albeit in different individuals. This result can be a consequence of the generalist foraging behaviour of kelp gulls, which take advantage of the multiple trophic resources available along the coast from both marine and estuarine habitats (Bahamondes & Castilla, 1986; Yorio et al ., 2013). Accordingly, kelp gulls present a high diversity of endoparasites, including cestodes, nematodes, trematodes and acanthocephalans (Torres et al ., 1991; Riquelme et al ., 2006; González-Acuña et al ., 2009; Diaz et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In order to answer the question of which parasite species (co-)occur in this parasitic system, we can suggest that, due to the differences in the prey item consumption and high mobility of seagulls (Smith, 2007;Yorio et al, 2013), both Profilicollis species could be found cooccurring in any of the definite hosts. On the other hand, intermediate host species occur in specific habitats and with little spatial overlap (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The bird species with the highest number of taxa of nematodes reported are Larus dominicanus (Laridae) and Nothura maculosa (Tinamidae) with 10 and 9 taxa reported, respectively. Larus dominicanus is an abundant species that inhabits a great diversity of environments and has a generalist and opportunistic diet (Yorio et al, 2013), which means that it would be more likely to acquire a wide variety of nematodes with indirect life cycle. In addition, the helminths of these birds have been studied in numerous opportunities, being also the bird species with the highest number of digenean species reported (see Lunaschi et al, 2007;.…”
Section: Discussionmentioning
confidence: 99%
“…The Olrog's Gull (Larus atlanticus) is a species endemic to the Atlantic coast of southern South America (BirdLife International 2018;Harrison 1984;Olrog 1967;Yorio et al, 1998), and along with L. fuliginosus and L. heermani constitutes the three threatened gull species listed in the entire American continent (BirdLife International 2018). The breeding range of L. atlanticus is restricted to only two nesting areas and 18 breeding colonies along 2500 km of the central Argentinean coast between 39 12 0 -45 11 0 S (Yorio et al, 2013). The main breeding area of the species is located in the Bahía Blanca estuary (García Borboroglu and Yorio 2007;Yorio et al, 1998), which is subject to intense human pressures ranging from urban development, industry, agriculture, recreation, fishing, pollution and even egging (Yorio et al, 2005(Yorio et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The breeding range of L. atlanticus is restricted to only two nesting areas and 18 breeding colonies along 2500 km of the central Argentinean coast between 39 12 0 -45 11 0 S (Yorio et al, 2013). The main breeding area of the species is located in the Bahía Blanca estuary (García Borboroglu and Yorio 2007;Yorio et al, 1998), which is subject to intense human pressures ranging from urban development, industry, agriculture, recreation, fishing, pollution and even egging (Yorio et al, 2005(Yorio et al, , 2013. The entire breeding population has been estimated at approximately 5000e8000 pairs (Yorio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%